Adaptive mesh refinement FEM for seismic damage evolution in concrete-based structures. (15th May 2016) - Sun, Bin; Li, Zhaoxia
Highlights: A method for simulating seismic damage process of concrete structures is proposed. The process from material damage to structural failure can be simulated. FE elements can be refined adaptively with damage accumulation. The simulated results fit well with the experimental results. Abstract: In order to study the seismic damage mechanisms of concrete-based structures, a adaptive multi-grid method is developed to simulate the process from evolving damage to structural failure in concrete structures under seismic loading. The theory of multi-grid FEM coupled evolving damage is developed on the basis of the improved variational principle, in which the elements in each sub-domain with different grid sizes are under the different state of damage. Meanwhile the FE elements can be refined adaptively with the accumulation of its damage for lower cost, without user intervention in the computation. As a case study of the method, the failure process of reinforced concrete column under seismic loading is simulated, the results show that, the simulated results fit well with the experiment, and the developed method can be used to reveal the seismic damage mechanism of concrete-based structures by considering the process from material damage to structural failure; the adaptive multi-grid method can give satisfactory result with lower cost by compared with experiment.